PENGEMBANGAN L-PERWUZ BERBASIS DIGITAL MENINGKATKAN SELF-REGULATED LEARNING DAN LITERASI SAINS SISWA KELAS IV SDN GADUNGAN 02 KABUPATEN BLITAR - Khoiriyah, Naimatul; Fatih, Mohamad; Oktaviani, Ragil Tri (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to improve students’ self-regulated learning and scientific literacy by developing L-Perwuz learning media on the topic of changes in states of matter. The research employed a Research and Development (R&D) method using the ASSURE development model. The experiment was conducted using a pretest–posttest design involving 16 students. Data were collected through tests and questionnaires. The results showed that the media expert assigned a validity score of 92% (valid category), the material expert gave a score of 85% (valid category), and the teacher rated the media feasibility at 95% (feasible category). Student responses toward the L-Perwuz media were positive. The media significantly improved students’ self-regulated learning, as indicated by the paired t-test results with a significance value of 0.000 < 0.05. In addition, the media also showed a significant effect on enhancing students’ scientific literacy, supported by paired t-test results with a significance value of 0.000 < 0.05. In conclusion, the L-Perwuz media is valid, feasible, and effective in improving students’ self-regulated learning and scientific literacy.